2021
DOI: 10.1101/2021.07.16.452571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular evolution and structural analyses of the spike glycoprotein from Brazilian SARS-CoV-2 genomes: the impact of the fixation of selected mutations

Abstract: The COVID-19 pandemic caused by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has reached by July 2021 almost 200 million cases and more than 4 million deaths worldwide since its beginning in late 2019, leading to enhanced concern in the scientific community and the general population. One of the most important pieces of this host-pathogen interaction is the spike protein, which binds to the human Angiotensin-converting enzyme 2 (hACE2) cell receptor, mediates the membrane fusion and is the majo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…It can induce immune escape with consequent reinfection and is associated with convalescent plasma therapy failure ( 4 ). We have previously shown that both substitutions are under strong positive selection ( 5 ). Since these mutations are present in other VOCs around the world, their emergence is evidence of convergent SARS-CoV-2 evolution ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can induce immune escape with consequent reinfection and is associated with convalescent plasma therapy failure ( 4 ). We have previously shown that both substitutions are under strong positive selection ( 5 ). Since these mutations are present in other VOCs around the world, their emergence is evidence of convergent SARS-CoV-2 evolution ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that both substitutions are under strong positive selection ( 5 ). Since these mutations are present in other VOCs around the world, their emergence is evidence of convergent SARS-CoV-2 evolution ( 5 , 6 ). K417T occurs in an important footprint for class I anti-RBD antibodies and has been associated to decrease neutralization activity for some monoclonal antibodies (mAb).…”
Section: Introductionmentioning
confidence: 99%